2019
DOI: 10.1039/c8cc09532a
|View full text |Cite
|
Sign up to set email alerts
|

BaCoO2+δ: a new highly oxygen deficient perovskite-related phase with unusual Co coordination obtained by high temperature reaction with short reaction times

Abstract: A pinch of oxygen: incorporation of small additional oxygen introduces partly square planar coordination into BaCoO2+δ.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 14 publications
(18 reference statements)
3
12
0
Order By: Relevance
“…From the NYQUIST plot a single depressed semicircle was observed which was fitted using a single R‐CPE (constant phase element). The room temperature conductivity of the sample was determined from the intercept on the X‐axis and calculated to be 2.89×10 −4 S cm −1 which is of the same order of magnitude as that of BaCoO 1.80 (OH) 0.86 [7] and three orders of magnitude higher than that of BaCoO 2+δ [2] . This is in agreement with what is expected from the presence of Co in a mixed oxidation state (+3/+4).…”
Section: Figuresupporting
confidence: 78%
See 3 more Smart Citations
“…From the NYQUIST plot a single depressed semicircle was observed which was fitted using a single R‐CPE (constant phase element). The room temperature conductivity of the sample was determined from the intercept on the X‐axis and calculated to be 2.89×10 −4 S cm −1 which is of the same order of magnitude as that of BaCoO 1.80 (OH) 0.86 [7] and three orders of magnitude higher than that of BaCoO 2+δ [2] . This is in agreement with what is expected from the presence of Co in a mixed oxidation state (+3/+4).…”
Section: Figuresupporting
confidence: 78%
“…This is in agreement with what is expected from the presence of Co in a mixed oxidation state (+3/+4). An activation energy of 0.21(1) eV was calculated from the slope of the Arrhenius plot (Figure 4a) indicating the dominance of electronic contribution to overall conductivity [2] …”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…Since SSZ40GO is a cubic perovskite, we can write its formula as SrSc 0.3 Zn 0.2 Ga 0.5 O 2.4 . Literature examples of perovskites with oxygen contents lower than ABO 2.5 are uncommon and typically found for compounds containing variable oxidation state transition metals (e.g., Ba 0.5 Sr 0.5 Co 0.8 Fe 0.2 O 3−δ where δ can be up to 1 depending on the p O 2 ) or in compounds like SrCuO 2 and SrFeO 2 which have the square-planar-based infinite layer structure. These are frequently made by low-temperature topotactic reduction of oxygen-rich phases. On the other hand, Takeda et al reported oxygen deficiency corresponding to the oxygen content of 2.45 (normalized to perovskite) in the Sr/Ba/Sc/Al/O system.…”
Section: Resultsmentioning
confidence: 99%